2008
DOI: 10.1364/oe.16.016431
|View full text |Cite
|
Sign up to set email alerts
|

Integrated multiple multi-photon imaging and Raman spectroscopy for characterizing structure-constituent correlation of tissues

Abstract: Histopathological imaging of tissues often requires extensive sample preparation including fixation and staining in order to highlight characteristic alterations associated with diseases. Herein, we report an integrated spectro-microscopy approach based on a combination of multi-modal multi-photon imaging and Raman micro-spectroscopy and demonstrate label-free characterization of the structure-constituent correlation of porcine skin. The multi-modal imaging allows the visualization of dermatological features w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…The latter parameter is a scalar that characterizes the relative values of the molecular invariant groupings in Eqs. (26), (31), and (33). Although the precise value of y will depend on the component values of the transition tensors, it can be shown that y is positive and limited to an upper bound of (n + 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter parameter is a scalar that characterizes the relative values of the molecular invariant groupings in Eqs. (26), (31), and (33). Although the precise value of y will depend on the component values of the transition tensors, it can be shown that y is positive and limited to an upper bound of (n + 1).…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used, complementary modes of measurement include second-harmonic generation, sumfrequency generation, coherent anti-Stokes Raman scattering, and Raman spectroscopy-all are frequently combined with multiphoton fluorescence. 33,34 While three-photon microscopy in particular has been less commonly studied than its two-photon counterpart, it is recognized that image contrast can be enhanced as the number of concerted photon interactions increases. 35,36 The incorporation of additional techniques can permit the visual sectioning of specific molecular domains within bulk material, expanding the potential for applying multiphoton imaging as a tool in structural diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, since the laser source required for nonlinear spectroscopy is similar to the sources used for the other one of nonlinear processes mentioned above, many di®erent combinations are available, and CARS has been extensively combined with phenomena such as SHG, THG or TPAF. 77,133 CARS-SHG has been used for several di®erent samples, such as Caenorhabditis Elegans, 134 the central nervous system, 135 or skin, 136 as shown for example in Fig. 5 where CARS and SHG have been measured simultaneously on cardiomyocyte cells.…”
Section: Nonlinear Spectroscopy Multimodal Implementationsmentioning
confidence: 99%
“…63 Jhan JW, Chang WT et al reported an integrated spectro-microscopy approach based on a combination of multimodal multi-photon imaging and Raman micro-spectroscopy and demonstrated label-free characterization of the structure-constituent correlation of porcine skin. 64 The multimodal imaging allows the visualization of dermatological features whereas Raman micro-spectroscopy enables the identification of their 'molecular fingerprints'. By obtaining both structural and molecular-level information of tissue constituents, this system can offer new insight into the patho-physiological status of tissues (Figs.…”
Section: Multimodality Microscopic Imagingmentioning
confidence: 99%